Knowledge and systems engineering proceedings of the sixth International Conference KSE 2014 - International Conference on Knowledge and Systems Engineering Hanoi, Vietnam) 2014; Nguyen, Viet-Ha; Le, Anh-Cuong; Huynh, Van-Nam; SpringerLink (Online service). (Cham Springer, 2014)
This volume contains papers presented at the Sixth International Conference on Knowledge and Systems Engineering (KSE 2014), which was held in Hanoi, Vietnam, during 9-11 October, 2014. The conference was organized by the University of Engineering and Technology, Vietnam National University, Hanoi. Besides the main track of contributed papers, this proceedings feature the results of four special sessions focusing on specific topics of interest and three invited keynote speeches. The book gathers a total of 51 carefully reviewed papers describing recent advances and development on various topics including knowledge discovery and data mining, natural language processing, expert systems, intelligent decision making, computational biology, computational modeling, optimization algorithms, and industrial applications.
Electronic reproduction.
Keywords: Expert systems (Computer science) -- Congresses; Information technology -- Congresses; Knowledge management -- Congresses; Knowledge representation (Information theory) -- Congresses; Image processing -- Congresses; Systems engineering -- Congresses; Human-computer interaction -- Congresses; Machine learning -- Congresses; Electronic books